Determinants of Capital Flight: Macroeconomic and Non-Macroeconomic Perspectives - Taufik Hidayat; Fadli, Faishal (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2026)
Studies on capital flight in developing economies often lack comprehensive post-pandemic analysis for the ASEAN-5 region. This study fills this gap by analyzing the determinants of capital flight in Indonesia, Malaysia, Thailand, the Philippines, and Vietnam (2010–2023). Using the World Bank’s residual method and a Fixed Effect Model (FEM), the research examines the impact of the Current Account-to-Export Ratio (RCAE), Budget Deficit Ratio, Inflation, and Control of Corruption. Findings reveal that strong external capacity (RCAE) significantly mitigates capital flight, whereas monetary instability (Inflation) exacerbates it via flight-to-safety mechanisms. The Budget Deficit Ratio proves statistically insignificant, suggesting investors prioritize fiscal credibility over nominal deficits. A critical anomaly appears where improved Control of Corruption significantly increases capital flight; this indicates that better governance facilitates licit capital outflows (normal capital outflow) due to shallow domestic financial markets. Policymakers must prioritize external stability and deepen financial markets to retain liquidity generated by improved governance.